2018
DOI: 10.1016/j.ijcard.2017.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-isolation guided titration of freeze duration in 3rd generation short-tip cryoballoon pulmonary vein isolation – Comparable clinical outcome and shorter procedure duration

Abstract: TTI-guided cryoenergy titration leads to reduced procedure duration and fluoroscopy time and appears to be as effective as a fixed ablation strategy. A single 2-minute freeze seems to be sufficient in case of short TTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…There was variability in ablation protocol including time of freeze and use of time to isolation that may impact ablation outcome. However, previous studies have shown the equivalent efficacy of single 3‐min freeze versus double 4‐min freeze and time to isolation strategy versus fixed ablation strategy . In patients with redo ablations, the high rate of vein reconnection per patient is likely due to selection bias as patients with one or two veins reconnected would have received RF and not been included in our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There was variability in ablation protocol including time of freeze and use of time to isolation that may impact ablation outcome. However, previous studies have shown the equivalent efficacy of single 3‐min freeze versus double 4‐min freeze and time to isolation strategy versus fixed ablation strategy . In patients with redo ablations, the high rate of vein reconnection per patient is likely due to selection bias as patients with one or two veins reconnected would have received RF and not been included in our study.…”
Section: Discussionmentioning
confidence: 96%
“…However, previous studies have shown the equivalent efficacy of single 3-min freeze versus double 4-min freeze and time to isolation strategy versus fixed ablation strategy. [45][46][47] In patients with redo ablations, the high rate of vein reconnection per patient is likely due to selection bias as patients with one or two veins reconnected would have received RF and not been included in our study. Many patients did not have continuous rhythm monitoring post-CBA and reliance on scheduled clinic ECGs, short-term Holter monitors, and patient symptoms may underestimate episodes of AF recurrence.…”
Section: Strengths/limitationsmentioning
confidence: 99%
“…The exclusion criteria were long-standing persistent AF, previous left atrial (LA) ablation, LA diameter > 55 mm, uncontrolled heart failure (NYHA class IV), and severe valvular disease. The first 224 patients were treated with a fixed freeze protocol and the last 395 patients were treated with a time to isolation guided freeze protocol [13,14].…”
Section: Study Populationmentioning
confidence: 99%
“…A luminal esophageal temperature of 15-20°C was the cut-off temperature, leading to abortion of the freeze cycle. Phrenic nerve function was monitored by phrenic nerve stimulation and detection of compound motor action potentials (CMAP), as well palpation of diaphragm contractions during ablation of the right sided PVs [13,14].…”
Section: Ablation Proceduresmentioning
confidence: 99%
“…56 Recently, several studies have investigated ways to reduce cryotherapy time. 65,66 Pott et al reported that CB ablation with TTI-guided cryoenergy titration could be non-inferior to the fixed CB ablation strategy. 66 Their TTI-guided CB ablation protocol was modified such that freeze duration was 120 s for TTI <30s, and 180 s for TTI 30-60 s, and the fixed CB ablation protocol included of carina regions after CB ablation ( Figure 5).…”
mentioning
confidence: 99%